2019
DOI: 10.1111/sji.12770
|View full text |Cite
|
Sign up to set email alerts
|

Chronic inflammation during osteoarthritis is associated with an increased expression of CD161 during advanced stage

Abstract: Increasing evidence suggests a role of inflammation during the pathogenesis of osteoarthritis (OA). The local and systemic inflammation was studied in 33 patients of different KL grades, grade2 (n = 11), grade3 (n = 6) and grade4 (n = 16). The levels of cytokines, adipokines and matrix metalloproteinases (MMPs) were measured in serum and synovial fluid (SF) by flow cytometry and ELISA, respectively. The frequency of T cells and CD161 expression was measured by flow cytometry. The levels of IL‐1β, IL‐6 and IL‐1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…Considering GAG as a direct product of MMP action on cartilage, the highest GAG in KL grade-II and III SFs was a clear indication of the maximum activity of MMPs at these grades [ 24 ]. Sachdeva et al [ 25 ] reported similar observation on the ethnically similar population as in the present study, wherein MMP-9 and MMP-13 were studied in SF of OA patients. The expression of both the MMPs was reported high in KL grade-II and KL grade-III SFs and subsides in KL grade-IV.…”
Section: Discussionsupporting
confidence: 84%
“…Considering GAG as a direct product of MMP action on cartilage, the highest GAG in KL grade-II and III SFs was a clear indication of the maximum activity of MMPs at these grades [ 24 ]. Sachdeva et al [ 25 ] reported similar observation on the ethnically similar population as in the present study, wherein MMP-9 and MMP-13 were studied in SF of OA patients. The expression of both the MMPs was reported high in KL grade-II and KL grade-III SFs and subsides in KL grade-IV.…”
Section: Discussionsupporting
confidence: 84%
“…Early studies reported that PAR2 expression was up-regulated by inflammatory mediators such as TNF-α, IL-1α and lipopolysaccharide (LPS) [22]. A growing body of evidences suggested that inflammation played a crucial role in OA pathogenesis [23]. Previous studies reported that PAR2-deficient mice exerted less cartilage degradation in experimental osteoarthritis [18,24].…”
Section: Discussionmentioning
confidence: 99%
“…During the course of OA, IL-1 produced by chondrocytes and synovial nucleated cells, activates MMP in cartilage, causing degradation of cartilage matrix [31]. Sachdeva et al reported that MMP-9 in SF and MMP-13 levels in serum and SF decreased in K-L grade 4 cases [32]. However, there is still need for studies evaluating biochemical biomarkers of different stages of GOA.…”
Section: Discussionmentioning
confidence: 99%